The concept of teaching clinical hemostasiology in internal medicine - V. S. Chulkov; O. A. Shumakova; N. K. Vereina; Vl. S. Chulkov; S. P. Sinitsyn (Кардиоваскулярная терапия и профилактика, 2022)
Modern professional education of internists is being updated at an intensive pace. This is primarily due to the fact that medicine and its technologies do not stand still, rushing into a high-tech future. In this regard, people have great hopes for highly effective conservative care, including for hematological diseases. Basic research on the mechanisms of blood clotting has greatly improved the knowledge of complex pathophysiology. These advances have led to a more complex decision-making process, which is reflected in the complex effect of hemostasis imbalance on the complement system, immunity and inflammation, and hence on the treatment of hemostasis disorders. Given this rapidly changing context, optimal educational activities are needed to disseminate knowledge among health professionals and develop their competencies in this field. Specialized professional associations can provide support and training offerings that facilitate access to relevant resources and tools to enable high-quality, up-todate basic and clinical research.